Big Data Technology Moderates the Effect of Financial Fundamentals on Firm Value in Indonesia's Technology Sector - Nicholas Renaldo; Vivi Elvina; Teddy Chandra; Kristy Veronica; Achmad Tavip Junaedi; Jahrizal Jahrizal (Universitas Pendidikan Ganesha, 2025)
The volatility of firm value in Indonesia’s technology sector—driven by fluctuating financial fundamentals such as leverage, liquidity, and profitability, alongside the accelerating role of big data adoption—highlights the urgent need to investigate how digital transformation moderates the relationship between financial indicators and firm value to ensure competitiveness and sustainability in capital markets. This research seeks to examine the impact of leverage, liquidity, and profitability on company valuation, with big data technology serving as a moderating variable, in technology sector firms listed on the IDX from 2019 to 2023. The advantage of this study lies in its focus on utilizing big data technology as a moderating variable assumed to influence corporate valuation. Secondary data were employed, and a purposive sampling technique was applied, resulting in a sample of 16 firms. Data were analyzed using multivariate linear regression and interaction regression analysis with SPSS software as the analytical tool. The results indicate that leverage has a positive impact on firm value, liquidity has a favorable effect on firm value, and profitability exerts a constructive influence on firm value. However, big data technology does not directly affect firm value, nor does it moderate the relationship between leverage and firm value or between liquidity and firm value. Nevertheless, big data technology strengthens the positive effect of profitability on firm value.